PEMBIMBINGAN TEKNIS PEMBUATAN BERBAGAI VARIAN PEMPEK KEPADA WIRAUSAHA BARU DI KOTA BAUBAU - Patadjai, Andi Besse; Aslan, La Ode; Nur, Andi Irwan; Ninda, Waode; Siang, Roslindah Daeng (Bina Bahari, 2023)
One of the processed fish that is very popular among culinary enthusiasts is pempek. This preparation is made by grinding fish meat and adding a certain amount of flour to form a dough that can be formed in various types, such as submarine pempek, adaan, lenjer and several other forms. The purpose of community service activities (PKM) is to provide guidance for the Bau-Bau community members in producing various variants of pempek as food products for families and for culinary-based souvenirs or entrepreneurial products. Pempek is a value added product from Andeande fish that have low economic value. The activities were attended by small entrepreneurs who were registered with the Cooperatives, Small and Medium Enterprises (UKM) agency. The results of this activity showed the success of the participants in producing several types of pempek, namely black pempek from squid blood, pempek green kelor leaves, pempek shrimp, pempek filled with rebon and several other variants.Pempek;  Bau-bau;  UKM;  culinary;  value added product